2021
DOI: 10.22141/2224-0713.5.107.2019.176700
|View full text |Cite
|
Sign up to set email alerts
|

Зміни рухових функцій у дітей iз церебральним паралічем після курсу інтенсивної нейрофізіологічної реабілітації: сліпе дослідження

Abstract: Background. Modern intensive interventions addressing multiple challenges in children with cerebral palsy are attracting clinicians' and researchers' attention. One of such methods is the intensive neurophysiological rehabilitation system (INRS)-a combination of interventions focusing on different functional goals, merged into one intensive course. The purpose of the study was to assess changes in gross motor functions, muscle spasticity and passive range of motion (PROM) in children with spastic forms of cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…It combines different active and passive modalities within a two-week treatment course and is aimed at different functional goals within the ICF model [11]. The latest research demonstrated improvement in gross motor functions and a decrease of muscle spasticity in children with CP undergoing treatment with INRS [13,14]. Improvement of the hand functions is also one of the most important targets of the INRS.…”
Section: Introductionmentioning
confidence: 99%
“…It combines different active and passive modalities within a two-week treatment course and is aimed at different functional goals within the ICF model [11]. The latest research demonstrated improvement in gross motor functions and a decrease of muscle spasticity in children with CP undergoing treatment with INRS [13,14]. Improvement of the hand functions is also one of the most important targets of the INRS.…”
Section: Introductionmentioning
confidence: 99%